ON SOME LARVAL AND JUVENILE FISHES FROM THE BENGAL AND ORISSA COASTS - Jones, S.; Pantulu, V.R. (Indian Journal of Fisheries, 2015)
The present account deals with a number of larval and juvenile fishes collected from the Bengal and Orissa coasts (Fig. 1) in 1952 and 1953 respectively. The collection from the Bengal Coast was made by the first author in 1952, while on a visit to the Sundarban areas of the 24 Parganas on board the M.F.V. Kerala of the West Bengal Fisheries Department and that from the Orissa Coast was made by the second author and Dr. V. G. Jhingran in 1953 on board the I.N.S. Investigator during one of its survey operations at the mouth of the Mahanadi. Our thanks are due to the West Bengal Fisheries Directorate and to the Indian Naval authorities for the faciUties given aboard their vessels and for the co-operation extended by their officers. We also thank Dr. V. G. Jhingran who was in charge of making the collections on board the I.N.S. Investigator